REVITALISASI TARI MOCAH BUNGA PUKOL TUJOH KECAMATAN SIMPANG DUA KABUPATEN KETAPANG PROVINSI KALIMANTAN BARAT - Yosefin Irinia Dita; Ismunandar Ismunandar; Regaria Tindarika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
The study was based on the disappearance of the Mocah Bunga Pukol Tujoh dance Subdistrict Simpang Dua District Ketapang West Borneo. The goal is to revitalize the Mocah Bunga Pukol Tujoh dance Kecamatan Simpang Dua Kabupaten Ketapang West Borneo. So that, it’s existence can return to society. Specifically in this reaserch, the problem ia described as reflecting the revitallization of the activities and activities of the revitallization of the Mocah Bunga Pukol Tujoh dance Subdistrict Simpang Dua Diatrict Ketapang Provinces West Borneo.The date-gathering technique in this study is observation, interview and documentation. Verifying data in this study is the use of extensions of observation and source triagulation. The data analysis during data collection. The action of this study was then met by sources known as Sudan, Mardani and Lukas. Then teach to dancer. The result of this reaserch was being able to reteach the Mocah Bunga Pukol Tujoh dance and make a video of dancing Mocah Bunga Pukol Tujoh Subdistrict Simpang Dua District Provices West Borneo.Keywords:Performance Form, Tari Mocah Bunga Pukol Tujoh